Numerical Study of Aerodynamic Characteristics of Airflow Around NACA 0012 and NACA 4412 Airfoils at Re = 170000 - Soetanto, Maria Fransisca; Sugianto, Sugianto; Hartono, Budi; Z, M Rizki (Jurnal Internasional Penelitian Teknologi Terapan, 2023)
In this paper, a numerical study of the aerodynamic characteristics using the CFD method of the two-dimensional flow around NACA 0012 and NACA 4412 airfoils at -10 degrees to 25 degrees of angle of attack operating at Re 170000 is presented. The formation of flow patterns, pressure distribution, pressure coefficient (Cp), lift coefficient (Cl), drag coefficient (Cd), moment coefficient (Cm), and skin friction coefficient distribution along the chord The Y+ wall value curve is a validation that the mesh formation is in accordance with the requirements, i.e., a Y+ wall value below 10 for viscous dominant flows and for Spalart-Allmaras turbulent model viscous. The geometry of NACA 0012 and NACA 4412 airfoils is created using SolidWork, and CFD analysis is carried out using Ansys Workbench 2018. The results show that the stall condition at NACA 0012 is at 15 degrees of angle of attack, while at NACA 4412 it is at 16 degrees. Under stall conditions, Cl of NACA4412 is approximately 13 percent higher than NACA 0012, while the value of Cd shows almost the same value for both NACA 0012 and NACA 4412.